2013
DOI: 10.1108/15736101311329133
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of multi‐cycle deformation of polymers with various deformation programs

Abstract: Purpose -The purpose of this paper is to compare mechanical response of polypropylene in multi-cycle tensile tests with strain-controlled and mixed deformation programs and to develop constitutive equations that describe quantitatively the experimental data. Design/methodology/approach -Multi-cycle tensile tests are performed on isotactic polypropylene with strain-controlled (oscillations between fixed maximum and minimum strains) and mixed (oscillations between a fixed maximum strain and the zero minimum stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This is a feature of the viscoelasticity of the semicrystalline polymer and indicative of a type of mechanical damage 33 . Further cyclic loading shows a monotonic change in stress with cyclic loading which appears to approach an asymptotic value 34 .…”
Section: Resultsmentioning
confidence: 92%
“…This is a feature of the viscoelasticity of the semicrystalline polymer and indicative of a type of mechanical damage 33 . Further cyclic loading shows a monotonic change in stress with cyclic loading which appears to approach an asymptotic value 34 .…”
Section: Resultsmentioning
confidence: 92%
“…The applications include (but are not limited to) polymer matrix for fiber‐reinforced composites, synthetic membranes for geotechnical engineering or ion batteries, or pipe applications (see recent reviews for more details). The semi‐crystalline polymers are the subject of many scientific researches aiming to understand and characterize their nonlinear elasto‐viscoplastic behavior and the associated deformation mechanisms under different and complex loading paths …”
Section: Introductionmentioning
confidence: 99%
“…Numerous experimental and theoretical studies have been reported last decades to characterize and model the plastic damage deformation under uniaxial tension, which induces important large strain deformation along with significant volume change that constitute the fundamental mechanical properties of ductile polymers . The most recent reported modeling approaches for semi‐crystalline polymers include the use of two‐phase or three‐phase microstructural models, homogenization procedures, rheological models integrating the physics of polymer chains, or multiscale computational approaches . They often led to moderately accurate results concerning the fully time‐dependent anisotropic response of such materials to complex loadings in large strains.…”
Section: Introductionmentioning
confidence: 99%